2015
DOI: 10.1042/cs20150193
|View full text |Cite
|
Sign up to set email alerts
|

Serum proprotein convertase subtilisin/kexin type 9 concentration is not increased by plant stanol ester consumption in normo- to moderately hypercholesterolaemic non-obese subjects. The BLOOD FLOW intervention study

Abstract: Proprotein convertase subtilisin/kexin type 9 (PCSK9) regulates low-density lipoprotein (LDL) cholesterol (LDL-C) metabolism by targeting LDL receptors for degradation. Statins increase serum PCSK9 concentration limiting the potential of statins to reduce LDL-C, whereas ezetimibe, inhibitor of cholesterol absorption, has ambiguous effects on circulating PCSK9 levels. Plant stanols also reduce cholesterol absorption, but their effect on serum PCSK9 concentration is not known. Therefore, we performed a controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Regardless of the absolute plasma concentrations of PCSK9, our findings are in line with most previous reports showing that PCSK9 varies with sex, with the exception of two studies that find no gender difference in small cohorts [22,23]. Indeed, we found that PCSK9 plasma concentration was higher in women than in men, in both the univariate and the multivariable analysis, and this result is in agreement with studies in large, ethnically diverse, general populations [7,18,24], in a large population-based sample of children and adolescents [25], and in diverse cohorts of patients with stable coronary artery disease (CAD) or ACS [26,27].…”
Section: Discussionsupporting
confidence: 92%
“…Regardless of the absolute plasma concentrations of PCSK9, our findings are in line with most previous reports showing that PCSK9 varies with sex, with the exception of two studies that find no gender difference in small cohorts [22,23]. Indeed, we found that PCSK9 plasma concentration was higher in women than in men, in both the univariate and the multivariable analysis, and this result is in agreement with studies in large, ethnically diverse, general populations [7,18,24], in a large population-based sample of children and adolescents [25], and in diverse cohorts of patients with stable coronary artery disease (CAD) or ACS [26,27].…”
Section: Discussionsupporting
confidence: 92%
“…In some studies, phytosterols and phytostanols have modestly reduced serum triglyceride levels especially in those subjects with slightly increased baseline concentrations [ 23 , 24 ]. Lipoprotein (a) concentration remains unchanged [ 9 , 25 ], and phytostanols do not affect serum proprotein convertase subtilisin/kexin type 9 concentration [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Simonen et al, in a randomized controlled double-blind trial in normal and hypercholesterolemic subjects, evaluated the effect of a 6 months consumption of vegetable-oil spread (20 g/day), enriched (plant stanol group) or not (control group) with plant stanols (3 g/day) as ester. The long-term intake of plant stanol esters reduced LDL-C by 7-10%, without affecting either PCSK9 plasma concentrations or the hepatic LDLR levels, indicating that plant stanol esters can lower LDL-C through inhibition of cholesterol absorption, without interfering with PCSK9 metabolism [46]. De Smet et al showed that an acute intake of plant stanol esters (0.25 mg cholesterol + 50 mg plant stanol esters dissolved in olive oil) in mice up-regulated mRNA expression of intestinal PCSK9 and LDLR, and their main transcription factor SREBP-2, whereas hepatic expression of these genes was down-regulated after 15 min following oral intake.…”
Section: Sterol/stanols and Vegetable Proteinsmentioning
confidence: 96%